Barcelona and SEAT, a History of Lost Opportunity: Corporate Marketing, Nation Branding, and Consumer Nationalism in the Automotive Industry. (10th August 2015) - RIUS-ULLDEMOLINS, JOAQUIM
Abstract : Why is there no SEAT Barcelona? Barcelona is a well-named place brand, but SEAT consciously has disassociated itself from its geographic origins. This seems rather strange decision if one takes into account the increasing importance of the place-of-origin effect in automotive industry. This article describes how SEAT has constructed its Spanish identity and hidden its Catalan-Barcelona origins, and discusses SEAT's own growing "denationalization" because of the acquisition by Volkswagen Group by using banal nationalism to gain the loyalty of the country's nationalist consumers and to fashion a corporate image in line with Spain's Marca España, or national brand. Through this decision, SEAT has lost the opportunity to associate itself with Marca Barcelona, a successful urban brand.